Local Wisdom-Based Discovery Learning on Students’ Higher-Order Thinking Skills: Pembelajaran Penemuan Berbasis Kearifan Lokal terhadap Keterampilan Berfikir Tingkat Tinggi Siswa - Nur Saibah Tambunan; Syarifah Widya Ulfa (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): In the 21st century, Higher Order Thinking Skills (HOTS) are crucial for fostering critical, creative, innovative, and independent learners, aligning with the Merdeka Curriculum’s vision. Background (Specific): Environmental change and conservation topics are particularly suited to HOTS development, especially when contextualized through local wisdom, yet such integration remains underexplored in Indonesian Madrasah Aliyah contexts. Knowledge Gap: Despite evidence supporting Discovery Learning and local wisdom separately, limited studies investigate their combined impact on HOTS in secondary education biology, particularly in schools rich in cultural-environmental practices. Aim: This study examines the effect of a local wisdom-based Discovery Learning model on Grade X students’ HOTS in environmental change and conservation at MAN 2 Model Medan. Results: Using a quasi-experimental pretest–posttest control group design, findings show a significant improvement in the experimental group’s HOTS (mean posttest = 87.7) compared to the control (67.3), with statistical tests confirming normality, homogeneity, and a significant effect (p < 0.001). Novelty: The study integrates culturally relevant local practices into a constructivist Discovery Learning framework to enhance HOTS in environmental education. Implications: These results suggest that embedding local wisdom within inquiry-based models can meaningfully boost analytical, evaluative, and creative thinking skills, offering a replicable strategy for culturally responsive science education.Highlight : Discovery Learning based on local wisdom effectively improves students' HOTS. The research data is normally distributed and homogeneous according to statistical tests. The average posttest score of the experimental class is higher than that of the control class. Keywords : Higher Order Thinking, Discovery Learning, Local Wisdom, Environment, Quasi-Experimental